Fostering participation motivation and multidisciplinary teamwork collaboration through hospital culture and team leadership in Chinese tertiary public hospitals—A cross-sectional study - Zhengnan Meng; Jiamin Tang; Jie Yang; Huaineng Wu; Linlin Cui; Simin Zhu; Xiaohe Wang; Xianhong Huang (PLoS ONE, 2025)
Many modern diseases require more than one discipline for effective treatment, making multidisciplinary teamwork (MDT) essential. However, research on MDT in tertiary public hospitals in China is limited. These large healthcare institutions require effective collaboration among various departments to manage complex cases. Therefore, this study examined the effects of hospital culture, team leadership, and participation motivation on the MDT behavior of healthcare professionals to enhance MDT and improve related services. We conducted a questionnaire survey of 425 multidisciplinary team members in tertiary public hospitals in Hangzhou. T-tests, analysis of variance, and hierarchical linear regression were used to analyze the state of healthcare professionals’ MDT behaviors and the associated factors. A path analysis using a Structural Equation Model was used to explore and verify the effects of hospital culture, team leadership, and participation motivation on MDT behavior, as well as their underlying mechanisms. The findings revealed significant positive effects of hospital culture, team leadership, and participation motivation on MDT behavior. An SEM path analysis confirmed that these factors directly influence MDT behavior. Moreover, hospital culture and team leadership indirectly affected MDT behavior through participation motivation. This study demonstrated that a positive hospital culture and team leadership significantly enhanced MDT, with participation motivation mediating this relationship. These findings suggest that hospital leadership should promote a proactive and harmonious hospital culture and facilitate the development of team leaders’ management skills. Furthermore, exploring diverse incentives to increase healthcare professionals’ motivation for participation is essential for advancing MDT.